1989
DOI: 10.2151/jmsj1965.67.5_757
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Land Breeze and Snowfall Enhancement at the Leading Edge

Abstract: A land breeze is frequently observed along the coastal region of the Ishikari Plain during the winter season. A land-breeze front is formed offshore between colder over-land air and warmer over-sea air. In this study, we mainly used a single Doppler radar to examine the structure of the land breeze and its effect on snow clouds. The vertical profile of wind velocity was divided into three layers: the landbreeze layer (*300m in depth), the shear layer and the prevailing wind layer. The frontal surface was steep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Takayabu (1992) reported the roll cloud caused by K-H instability. Wakimoto et al (1992) observed K-H waves in a warm frontal rain band using a airborne Doppler radar, and Tsuboki et al (1989) analyzed K-H waves along the interface of land breeze and prevailing wind within snow clouds using a Doppler radar. Wang et al (1983) discussed the Ri in the vicinity of the rainband, where the atmosphere is in a saturated or near-saturated condition.…”
Section: Resultsmentioning
confidence: 99%
“…Takayabu (1992) reported the roll cloud caused by K-H instability. Wakimoto et al (1992) observed K-H waves in a warm frontal rain band using a airborne Doppler radar, and Tsuboki et al (1989) analyzed K-H waves along the interface of land breeze and prevailing wind within snow clouds using a Doppler radar. Wang et al (1983) discussed the Ri in the vicinity of the rainband, where the atmosphere is in a saturated or near-saturated condition.…”
Section: Resultsmentioning
confidence: 99%
“…This convergence enhances the development of clouds during night and early morning hours. Tsuboki et al (1989) also reported that the land breeze strongly influenced the precipitation distribution and snowfall could be enhanced due to the land breeze. On the contrary, when winds blow from the sea during daytime, the reverse situation occurs, which causes precipitation to decrease in the bay area.…”
Section: Possible Causes Of the Diurnal Cyclementioning
confidence: 93%
“…During winter in Japan, precipitation (including snowfall) distribution changes largely by synopticscale and mesoscale circulations, although topographical features also play an important role in varying the characteristics (Tachibana 1995). Ishihara et al (1989) showed the development of mesoscale snow clouds associated with land breeze and winter monsoon flow, and Tsuboki et al (1989) studied a winter land breeze and its effect on snow clouds. However, the land-sea breeze in the above studies is described as a more seasonal feature than a diurnal one driven by the seasonal land-sea temperature contrast, and can be observed at any time of the day.…”
Section: Introductionmentioning
confidence: 99%
“…Simpson et al (1977) suggested that the mixing is due to Kelvin-Helmholtz instability on the sea breeze fronts. Fujiyoshi et al (1988) and Tsuboki et al (1989) have reported that KelvinHelmholtz instability waves occure along a landbreeze frontal surface and that the wavelength is *1 km. In the case of a cold frontal type, the RHV display showed the occurrence of Kelvin-Helmholtz instability waves whose wavelength was 1-2km.…”
Section: B Movement Of the Land-breeze Frontmentioning
confidence: 99%